Identifikasi Gangguan pada Kompresor Udara Terhadap Kelancaran Pengoperasian Kapal di MV. Maluku 8 - Priyanto, Tegar; Khaeroman, Khaeroman; Suharso, Arif Rakhman; Putranto, Wahyu Ari (PPPM Polimarin, 2023)
Air compressors are auxiliary machines on board that produce compressed air on board. Compressed air is used as starting air for the main engine when the ship is about to perform maneuvers. On the MV. Maluku 8 there has been a leak in the air reservoir safety valve, where the pressure in the bottle is lacking while the air compressor is working continuously, this will result in damage to the air compressor. This research was conducted using descriptive methods and data collection techniques and interviews that aim to describe the actual situation in fact encountered in practice. Based on the results of the research, while the writer was carrying out the practice, a safety valve leak was found in the air tube (reservoir) due to dirt in the valve. The problem solver of this problem is to provide parts to the savety valve. To maximize performance and prevent air leaks in the compressor system at MV Maluku 8, there are several recommended corrective actions to expedite the performance of the main engine, including maintenance of the air compressor according to the provisions applied and proper PMS implementation.